A text message intervention for alcohol risk reduction among community college students: TMAP - Bock, Beth C. (Addict Behav, 2016)
BACKGROUND: Students at community colleges comprise nearly half of all U.S. college students and show higher risk of heavy drinking and related consequences compared to students at 4-year colleges, but no alcohol safety programs currently target this population. OBJECTIVE: To examine the feasibility, acceptability, and preliminary efficacy of an alcohol risk-reduction program delivered through text messaging designed for community college (CC) students. METHODS: Heavy drinking adult CC students (N = 60) were enrolled and randomly assigned to the six-week active intervention (Text Message Alcohol Program: TMAP) or a control condition of general motivational (not alcohol related) text messages. TMAP text messages consisted of alcohol facts, strategies to limit alcohol use and related risks, and motivational messages. Assessments were conducted at baseline, week 6 (end of treatment) and week 12 (follow up). RESULTS: Most participants (87%) completed all follow up assessments. Intervention messages received an average rating of 6.8 (SD = 1.5) on a 10-point scale. At week six, TMAP participants were less likely than controls to report heavy drinking and negative alcohol consequences. The TMAP group also showed significant increases in self-efficacy to resist drinking in high risk situations between baseline and week six, with no such increase among controls. Results were maintained through the week 12 follow up. CONCLUSIONS: The TMAP alcohol risk reduction program was feasible and highly acceptable indicated by high retention rates through the final follow up assessment and good ratings for the text message content. Reductions in multiple outcomes provide positive indications of intervention efficacy.